The concepts of «property», «strength», «power» in the semantic structure of the semantic-etymological field ‘property’ (on the material of the Russian language) - Ivanchikova, Julia S. (Journal of the Belarusian State University. Philology, 2018)
The article is devoted to revealing and researching the specifics of the cognitive connection between the concepts of«property», «strength», «power» in the structure of such an association as a semantic-etymological field. The concepts under consideration have a basic character for Russian speakers (most likely, they are universal). The material of the Russian language reveals a number of etymological nests entering the semantic-etymological field of ‘property’, the com- ponents of which reveal the syncretism of the concepts «property», «strength», «power» (nests with the roots *seb-/*sob-, * vel-/*vol-, *im-, *bog-, *tȩg-). As a result of the analysis of linguistic material, a conclusion is made about the regularity and metonymic nature of the connection of these concepts.
Keywords: semantic-etymological field; concept; property; strength; power; semantic connection; etymological nest; root reflex